CHANGES FROM NORMALITY IN PATIENTS WITH DOWN SYNDROME: AN INTEGRATIVE LITERATURE REVIEW - Caroline Ribeiro Lacerda, Anne; Pedro Silva Pires, Antonio; César Ferreira Gomes, Júlio; Gama de Oliveira Muniz , Letícia; Suammi Lima de Carvalho, Ilana; Carvalho Rodrigues, Jamilly; de Araújo Machado Borges, Mariana; Rodrigues Silva , Nicole; Roberio Gomes Pereira de Souza, Thawan; de Souza Pereira, Malvina (Health and Society, 2025)
Patients with Down syndrome commonly exhibit deviations from physiological patterns, which may result from genetic, behavioral and environmental factors, leading to dental anomalies, delayed tooth eruption, malocclusions, increased predisposition to dental caries, tooth sensitivity and the presence of fissured tongue. This study aims to gather and synthesize evidence on changes in normality in patients with Down syndrome, providing a comprehensive understanding of the subject. To develop this integrative literature review, the following databases were used: U.S. National Library of Medicine (Pubmed), Virtual Health Library (BVS) and Scientific Electronic Library Online (Scielo), including articles and papers that deal with the presented theme published in the last 10 years, in Portuguese, English and Spanish, that addressed the proposed theme. The studies analyzed demonstrate that individuals with this condition present oral alterations that compromise both masticatory function and aesthetics, thus requiring detailed dental planning, with a focus on functional rehabilitation and improving self-esteem. Thus, understanding these changes becomes essential to ensure adequate management and treatment by health professionals, especially dentists, since hygiene difficulties, dental problems and a greater predisposition to periodontal diseases are present in this population.